AN ANALYSIS OF VOCABULARY MASTERY OF EIGHT GRADES STUDENTS AT SMP AMALYATUL HUDA MEDAN - Chris Yovie Sitorus; Mujur Simanjuntak; Sovicana Liontine Sinaga; Natalia Widya Pasca Tarigan (PROJECT (Professional Journal of English Education), 2021)
This study aims an analysis of the student's command of vocabulary. The method used to conduct this study was qualitative design. The data collection for this report, another significant document on the method includes observations, interviews, and testing. The sample used in this paper is 20 students in the eighth grade, one English teacher at SMP SWASTA AMALYATUL HUDA MEDAN. The results showed that the vocabulary of students in Grade 8 was very low, based on an analysis of the data, after the researcher did the study. And the researchers suggest that the English teacher should change the techniques and learning habits to incorporate and expand the vocabulary of students and still make those students feel not bored and difficult, but rather benefit from learning the English language. Keywords:  Analysis, Vocabulary Mastery